Alternative Media and Nonlinear Mediated Debate: The Case of Variety Streamers - Atkinson, Joshua (Javnost-The Public, 2023)
Past research has noted that alternative media often facilitate debate between activists and advocates for political policies. However, such research does not typically address the processes for those debates. In recent years, political influencers have increasingly made debates important content in the alternative media they produce through streaming services. In 2021, I observed a debate between three influencers that took place through YouTube and Twitch. In this research project, I engaged in a qualitative content analysis of key texts, using concepts concerning debate from past political communication research. Specifically, I examined the pre-debate, debate and post-debate stages in order to identify different attacks, acclaims or defences utilised by the influencers. The findings, viewed through the lens of mediated construction of reality described by Couldry and Hepp, demonstrate that those linear stages established in past campaign research do not fully apply to the context of alternative media found on streaming services. Instead, this debate was a nonlinear process in which the “pre-debate” stage was actually the debate.